Efficacy of Osteoconductive Ceramics in Bioresorbable Screws for Anterior Cruciate Ligament Reconstruction: A Prospective Intrapatient Comparative Study. Issue 5 (30th May 2016) - Barth, Johannes; Akritopoulos, Panagiotis; Graveleau, Nicolas; Barthelemy, Renaud; Toanen, Cécile; Saffarini, Mo
Background: Osteoconductive additives are used in resorbable interference screws for anterior cruciate ligament (ACL) reconstruction to improve graft incorporation and mitigate adverse effects. There are no published studies that compare biological performances of bioresorbable and biocomposite screws without artifacts due to different follow-up times and intrinsic patient characteristics. Purpose/Hypothesis: The purpose of this study was to evaluate the efficacy of osteoconductive agents in bioresorbable screws for ACL reconstruction at minimum follow-up of 2 years by intrapatient comparison. The hypothesis was that osteoconductive ceramics would result in slower resorption, improved ossification, and less tunnel widening. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 28 ACL reconstructions at 2 centers were randomly assigned into 2 comparable groups: (1) the graft was fixed in the tibia using standard bioresorbable screws and in the femur using biocomposite screws with osteoconductive agents (biphasic calcium phosphate), and (2) the graft was fixed in the femur using a standard bioresorbable screw and in the tibia using a biocomposite screw with osteoconductive agents. Results: Twenty-seven patients completed evaluations at 29.9 ± 4.0 months. Resorption was complete for more bioresorbable (81%) than biocomposite (37%) screws ( P = .0029), whereas satisfactory ossification was observed in more biocomposite (52%) than bioresorbable (15%) screws ( P = .0216). The tunnel shape was normal in more biocomposite (81%) than bioresorbable (48%) screws ( P = .0126), and marked cortical formation was twice more frequent for biocomposite (78%) than bioresorbable (37%) screws ( P = .0012). Bioresorbable screws exhibited faster resorption in the femur ( P = .0202) but not in the tibia (not significant). Conversely, biocomposite screws demonstrated better ossification, less tunnel widening, and more cortical formation in the tibia ( P < .0001, P = .0227, and P < .0001, respectively) but not in the femur (not significant for all). Conclusion: Osteoconductive additives can reduce the extent of resorption while improving ossification, reducing tunnel widening, and increasing cortical formation. Clinical Relevance: The benefits of osteoconductive agents justify their associated costs for ACL reconstruction, particularly in the tibia.